If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + 7b = 11 Solving 4a + 7b = 11 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7b' to each side of the equation. 4a + 7b + -7b = 11 + -7b Combine like terms: 7b + -7b = 0 4a + 0 = 11 + -7b 4a = 11 + -7b Divide each side by '4'. a = 2.75 + -1.75b Simplifying a = 2.75 + -1.75b
| 6x-9x-5= | | -25d=49 | | y^6-4=2 | | 34z=-56 | | 3a+4b+2a-2b= | | 6r-3= | | 4y-8+y+36=6y+30-3y | | 20y+20=-40 | | xy-2=4w | | 7(8+k)=21 | | 200-2x=18 | | .02x+.09(100-x)=6.2 | | -9(7a+6)=34 | | 8r+5=38r+10 | | (x)(y-4)=96 | | G-0.21G-0.08G=987.61 | | 2a+85=685 | | 49v^2-49v+9=0 | | 70=50+50*r*10 | | =4x^3-32x^2+64x | | 7r-8r=21 | | -3.3x+9.2=6.8+12.7x | | 8-(2y+3)=3-3y | | 8x+16=-64 | | 29x+3y+90=180 | | 19+(10x+1)=90 | | 3(2z+z)= | | 2x-21=21 | | 6(4+x)= | | 6z=z+5z | | 2=-2x+8 | | (2w-3)w=35 |